Peran Konseling Individu dalam Membantu Mengatasi Masalah Inner Child Akibat Pola Asuh Otoriter - Rismahani Manik; Erfina E; M. Kamal Al Fata Barus; Ainul Mardiyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Authoritarian parenting, characterized by strict control, high demands for compliance, and minimal emotional support, can lead to emotional wounds in childhood (inner child) that persist into adulthood. This condition results in low self-confidence, anxiety, difficulty managing emotions, and barriers to expressing feelings. This study aims to describe the forms of inner child problems resulting from authoritarian parenting, the individual counseling process used to help overcome these problems, and the changes experienced by clients after individual counseling. The study used a qualitative, descriptive approach. The subjects consisted of three individuals with a history of authoritarian parenting and who had participated in individual counseling services. Data were collected through in-depth interviews, observations during the counseling process, and counseling notes. The results indicate that individual counseling plays a crucial role in helping clients understand inner child wounds, validate repressed emotions, and increase self-awareness and self-acceptance. After counseling, clients demonstrated improved emotional regulation skills, increased courage to express feelings, and decreased anxiety.